(untitled) (Zoological Records and Reviews, 2022)
The Bay of Bengal coastline, extending approximately 2,090 km along the eastern coast of India from West Bengal to Tamil Nadu, encompasses highly diverse marine and intertidal habitats including rocky shores, sandy beaches, estuarine mudflats, seagrass beds, and coral reef patches. Marine gastropods (Class Gastropoda) constitute a major component of the benthic molluscan fauna in these habitats, performing critical ecosystem functions as grazers, predators, and detritivores. Despite their ecological importance and commercial value, the gastropod fauna of the Bay of Bengal coast of India has not been comprehensively evaluated since the monographic work of Hornell and Tomlin (1934). This study presents a systematic taxonomic evaluation of marine gastropods from 52 survey localities spanning the Indian Bay of Bengal coastline, sampled during 2019-2021 across four habitat types. A total of 312 gastropod species from 84 families and 148 genera are documented, including 48 new records for the Indian Bay of Bengal coast and 12 candidate new species. The families Muricidae (38 species), Conidae (34 species), and Cypraeidae (28 species) are the most species-rich. Southern survey sites in Tamil Nadu show significantly higher species richness than northern sites in West Bengal and Odisha, consistent with the Indo-Pacific marine biodiversity gradient. Updated morphological diagnoses and distribution maps are provided for all newly recorded species. Eighteen species are assessed as IUCN Threatened or Near Threatened, with overcollection for the ornamental shell trade identified as the primary conservation threat.